Kızılırmak Deltası Kıyı Çizgisinin EPR ve LRR Yöntemleriyle 1984–2022 Periyodunda Değişim Analizi ve 2030 Yılı Tahmini - Derya Öztürk; Sibel Uzun (Coğrafi Bilimler Dergisi, 2023)
Determining shoreline changes, investigating the reasons for these changes, and making predictions for the feature are of great importance for coastal management. The aim of this study is to analyze shoreline changes in an 8 km-long region of the Kızılırmak Delta during the period 1984–2022 and predict the shoreline for the year 2030. The shorelines were determined using Landsat-5 TM/Landsat-8 OLI/Landsat-9 OLI-2 satellite images of 1984, 1990, 1996, 2002, 2008, 2015 and 2022. Annual shoreline change rates were calculated using the EPR and LRR methods. For the period 1984–2022, EPR revealed an average erosion rate of -7.0 m/year, with a maximum erosion rate of -16.2 m/year. LRR showed an average erosion rate of -7.5 m/year, with a maximum erosion rate of -19.6 m/year. The total area lost due to erosion was 201.40 hectares, and 57% of the 8 km coast according to EPR and 50% according to LRR showed high degree of erosion. The results revealed that the coastal protection structures could not completely prevent the erosion. Without necessary precautions, it is predicted that an additional 51.48 hectares of area may be lost due to erosion by 2030, potentially reaching depths of -270.8 m.